Performance of CO2 and Fe-modified lignin char on arsenic (V) removal from water. (September 2021) - Cha, Jin Sun; Jang, Seong-Ho; Lam, Su Shiung; Kim, Hyungjoo; Kim, Young-Min; Jeon, Byong-Hun; Park, Young-Kwon
Abstract: Biochar was produced by the pyrolysis of Kraft lignin at 600 °C followed by modification with CO2 at 700 and 800 °C and impregnation with FeOx. The physicochemical properties and arsenic (V) adsorption performance of biochar were evaluated. The characteristics of the lignin biochar before and after CO2 modification and FeOx impregnation were analyzed using the following methods: proximate and ultimate analysis, specific surface area (Brunauer–Emmett–Teller (BET) surface area), porosity, scanning electron microscopy and energy dispersive spectroscopy mapping, Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy. The specific surface area and porosity of biochar were improved significantly after CO2 modification. However, impregnation of FeOx in CO2 -modified biochar showed a 50%–60% decrease of BET surface area and porosity due to pore blocking of FeOx. The batch adsorption of arsenic (V) showed that FeOx-LC-800 (FeOx impregnation lignin char modified with CO2 at 800 °C) had the highest adsorption efficiency among the biochars tested because of its highest Fe–O intensity and large surface area. The Langmuir adsorption model was suitable for the curve fitting arsenic (V) adsorption. The theoretical equilibrium adsorption amount ( q e ) was calculated to be 6.8 mg/g using a pseudo-second-order kinetic model. Graphical abstract: Image 1 Highlights: CO2 activation lignin char did not have a high As (V) adsorption efficiency. FeOx loaded lignin char showed higher efficiencies for the adsorption of As (V). The Langmuir model was suitable for the As (V) adsorption on modified lignin char. The maximum As(V) adsorption capacity of FeOx loaded lignin was 800 mg/g.